Assessment of denture hygiene habits among the denture wearers visiting a tertiary hospital of Nepal - Maharjan, Anjana; Verma, Anand; Shrestha, Rachana; K.C., Neela; Pradhan Joshi, Sarita (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Denture plaque is a dense layer of microorganism developed on surfaces of prosthesis. This plaque usually harbors various bacteria and fungus which can cause infections. For cleaning denture various cleaning regimens are used such as denture cleaners, soap. Various researchers have found that denture brushing is the most common practice among denture wearers but approximately 50% of them do not remove prosthesis overnight. The aim of our study was to assess denture hygiene practice among denture wearers. Methods: A descriptive cross- sectional study was done in Patan Academy of Health Sciences with convenience sampling in the people wearing denture. Data collection was done by face to face interview and clinical examination.These collected data was entered and analyzed in Excel to find out prevalence of denture hygiene habits. Results: Most of study participants 283(74.10%) wore interim removable partial denture. All of the study participants cleaned their denture. Of them, majority 181(47.40%) cleaned their denture once a day. Most of the study participants 330(86.40%) removed denture at night and 13.60% did not remove denture at night. 46(12%) of our study group did not remove prosthesis while brushing. Of those who removed prosthesis while brushing used soap for cleaning. Conclusions: All our study population cleaned denture, majority of them cleaned denture once a day with soap water and brush, small number of people didn’t remove the denture at night and while cleaning. This denture hygiene practice concludes the need of awareness of denture hygiene practice to denture wearer for good oral hygiene.